2021
DOI: 10.1016/j.molmet.2021.101294
|View full text |Cite
|
Sign up to set email alerts
|

Physiological impact of in vivo stable isotope tracing on cancer metabolism

Abstract: Background There is growing interest in the analysis of tumor metabolism to identify cancer-specific metabolic vulnerabilities and therapeutic targets. Finding of such candidate metabolic pathways mainly relies on the highly sensitive identification and quantitation of numerous metabolites and metabolic fluxes using metabolomics and isotope tracing analyses. However, nutritional requirements and metabolic routes used by cancer cells cultivated in vitro do not always refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 103 publications
(160 reference statements)
0
8
0
Order By: Relevance
“…After glutamine injection, healthy pancreas, tumor tissue, and plasma samples were collected, and 15 N enrichment in arginine and arginine biosynthetic precursors was measured by LC–MS ( Figure 2—source data 2 ). Glutamine in plasma is also quickly metabolized by multiple organs, which can then release labeled arginine and other metabolites into the circulation, which contribute to arginine labeling in other organs and the tumor ( Grima-Reyes et al, 2021 ). One of the main examples of these interorgan exchange fluxes is the intestinal–renal axis, where glutamine metabolized by the small intestine is released as citrulline, which is then used by the kidneys to produce arginine for other tissues ( Boelens et al, 2005 ; Grima-Reyes et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…After glutamine injection, healthy pancreas, tumor tissue, and plasma samples were collected, and 15 N enrichment in arginine and arginine biosynthetic precursors was measured by LC–MS ( Figure 2—source data 2 ). Glutamine in plasma is also quickly metabolized by multiple organs, which can then release labeled arginine and other metabolites into the circulation, which contribute to arginine labeling in other organs and the tumor ( Grima-Reyes et al, 2021 ). One of the main examples of these interorgan exchange fluxes is the intestinal–renal axis, where glutamine metabolized by the small intestine is released as citrulline, which is then used by the kidneys to produce arginine for other tissues ( Boelens et al, 2005 ; Grima-Reyes et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Glutamine in plasma is also quickly metabolized by multiple organs and reintroduced into the circulation as intermediate substrates that can contribute to intraorgan and intratumoral labelling (Grima-Reyes et al, 2021). One of the main examples of these interorgan exchange fluxes is the intestinal-renal axis, where glutamine metabolized by the small intestine is released as citrulline and uptaken by the kidneys and further released as arginine for uptake by different tissues (Boelens et al, 2005; Grima-Reyes et al, 2021). Consistent with this, we observed an enrichment of ∼14% 15 N 1 -arginine and ∼7% 15 N 2 -arginine in the circulation of healthy and tumor bearing mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, a recent comparison of metabolic flux analysis demonstrated that glucose metabolism in 3D spheroids differs significantly from 2D cultures (Tidwell et al, 2022), hence emphasizing the need to make use of 3D models for investigating cancer metabolism and drug response in cell culture. In this regard, in vivo profiling of tumor metabolic routes within the appropriate tissue environment will be key for interrogating drug action in human cancers (Lane et al, 2016) and to identify relevant alterations that contribute to cancer onset and progression (Grima-Reyes et al, 2021). While the adaption Frontiers in Molecular Biosciences frontiersin.org capability to different biological systems is one aspect of our workflow, usage of different tracers can also be readily implemented to gain complementary information (e.g.…”
Section: Discussionmentioning
confidence: 99%